THE INFLUENCE OF FAMILY ENVIRONMENT ON THE YOUTH PERSONALITY BUILDING : (A SURVEY STUDY AT SMA NAHDLATUL WATHAN JAKARTA) - Syahrul Faidzin (Scientia Integritas Utama, 2022)
The family environment is the first and foremost milieu that affects the development and behavior of children. In the family environment, children get attention, affection, encouragement, guidance, role models, and the fulfillment of economic needs from parents to develop all their potential for future development. In this study, there are two variables, namely: the influence of family environment, variable X, while the second variable is youth personality building as variable Y.The research is located at SMA Nahdlatul Wathan Jakarta on Jl. Kebon Raya, RT04/RW03 No. 1 East Jakarta, Milling, East Cakung. The population in this study was the students of SMA Nahdlatul Wathan Jakarta 2022/2023, totaling 83 students in class X totaling 32 students/I, class XI totaling 32 students/I, Class XII totaling 19 students/i. The used method used applies to the quantitative correlation method. There are 83 students in SMA NW Jakarta using a simple random sampling method. The results showed that when viewed from the point of view of the product-moment coefficient test, it produced